Sustainable campus and academic staffs awareness and behaviour in Malaysia’s institutions of higher learning: a case study of UPSI - Nor Kalsum Mohd Isa, (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
The concept of sustainable development has gained global attention since its introduction through the Bruntland Report 'Our Common Future' during the United Nations Conference on Environment and Development in 1987. In line with the recommendations of the government to encourage the development of sustainable campuses in Malaysia, Universiti Pendidikan Sultan Idris (UPSI) has initiated several steps towards to realize this goal. However, the effective implementation of a sustainable campus must begin with the awareness and support from the campus community itself. This study examined the level of awareness among UPSI academic staffs with regard to the principles of a sustainable campus. It analysed the relationship between the knowledge, attitude and behaviour of the academic staffs with the level of their awareness of the sustainable campus principles . Primary data were obtained through a questionnaire survey of randomly sampled186 academic staffs. Results of the correlation tests showed a high awareness level (mean value of 4.36) of the UPSI academic staffs with regard to the principles of a sustainable campus. However, there was a weak correlation between their awareness level and their behaviour (r = 0.464). This led to the conclusion that the UPSI academic staffs’ high awareness of the desirability of a sustainable campus did not prompt them to act positively towards the implementation of the sustainability principles at UPSI.